Respuesta :
12(2x - 8) = 4(5 - 2x) + 3(7 - 3x)
24x - 96 = 20 - 8x + 21 - 9x
24x - 96 = - 17x + 41
24x + 17x = 41 + 96
41x = 137
x = 137/41 <==
24x - 96 = 20 - 8x + 21 - 9x
24x - 96 = - 17x + 41
24x + 17x = 41 + 96
41x = 137
x = 137/41 <==
Simplify both sides of the equation:
12(2x − 8) = 4(5 − 2x) + 3(7 − 3x)
(12)(2x) + (12)(−8) = (4)(5) + (4)(−2x) + (3)(7) + (3)(−3x) *Distribute*
24x + −96 = 20 + −8x + 21 + −9x
24x − 96 = (−8x + −9x) + (20 + 21) *Combine Like Terms*
24x − 96 = −17x + 41
*Add 17x to both sides.*
24x − 96 + 17x = −17x + 41 + 17x
41x − 96 = 41
*Add 96 to both sides.*
41x − 96 + 96 = 41 + 96
41x = 137
*Divide both sides by 41.*
41x/41=137/41
x=137/41
12(2x − 8) = 4(5 − 2x) + 3(7 − 3x)
(12)(2x) + (12)(−8) = (4)(5) + (4)(−2x) + (3)(7) + (3)(−3x) *Distribute*
24x + −96 = 20 + −8x + 21 + −9x
24x − 96 = (−8x + −9x) + (20 + 21) *Combine Like Terms*
24x − 96 = −17x + 41
*Add 17x to both sides.*
24x − 96 + 17x = −17x + 41 + 17x
41x − 96 = 41
*Add 96 to both sides.*
41x − 96 + 96 = 41 + 96
41x = 137
*Divide both sides by 41.*
41x/41=137/41
x=137/41